Gyrotatic dynamics of magneto viscoelastic material with thermal and solutal transport - Muhammad; Masood Khan; A.S. Alqahtani; M.Y. Malik (Case Studies in Thermal Engineering)
Non-Newtonian fluids are essential in advanced engineering applications and industries because they exhibit unique flow behavior. This adaptability allows engineers to enhance efficiency and develop innovative solutions across diverse applications. The current investigation is focused on MHD Maxwell fluid flow across a spinning disk. A radially stretching phenomenon along with the permeability surface is considered. Generalization of the widely used von Karman viscous pump for configuration with gyrotatic microorganisms is also present. The influence of nonlinear thermal radiation, heat source, and Arrhenius kinetic effects in thermal and solutal transports are investigated. Furthermore, the temperature also depends on the thermal conductivity. The controlling model of the governing equations is converted from partial differential equations into dimensionless form in terms of ordinary differential equations by using the similarity transformations approach. The Maple symbolic software obtains numerical solutions for the resulting nondimensional physical parameters. The effects of physical parameters such as Deborah number, permeability parameters, magnetize field, Prandtl number, chemical reaction parameter, activation energy, and Lewis number are investigated on the fluid flow, temperature, concentration, and motile density profiles. These are depicted in graphical forms which contribute to advancing our understanding of the fluid dynamics of our problem. Furthermore, friction drag, thermal and solutal energy transportation rates and motile density are investigated numerically through tabular forms. It is also observed that the rate of thermal transfer increases significantly with disk rotation (ϖ) and radiation (Rd) parameters. Additionally, the Schmidt number (Sc) and chemical reaction parameters are fundamental in boosting the Sherwood number. The present work shows strong agreement when compared with previously published results in the literature.